Coping with drought : farmers' actions and public policies in Suphanburi Province, Thailand - Surutwadee Pak-Uthai; Faysse, Nicolas; Shrestha, Rajendra Prasad; Soni, Peeyush; Kuwornu, John K. M.; Ministry of Agriculture and Cooperatives (MOAC), Thailand; Asian Institute of Technology Fellowship (Pathum Thani : Asian Institute of Technology, 2019)
Abstract The drought in 2015 - 2016 was a major hydrological drought that hit many regions of Thailand, and especially the Chao Phraya River Basin, which is the largest river basin in Thailand. Suphanburi Province is the province that has the largest irrigated area in Thailand. During the drought, the Royal Irrigation Department provided water only for drinking water and stopped providing water to irrigation canals for agricultural production in Suphanburi Province. In this province, most farmers had never experienced a hydrological drought of such an extent. Thi~earch aims to understand how farmers dealt with this drought, and how government policies were designed and implemented at the provincial level. More specifically, the study examines (1) the diversity of adaptive measures taken by farmers, and to what extent the different measures were applied simultaneously; (2) the effect of adaptive measures on farming households' capacity to obtain income during drought and on households' financial situation at the end of the drought; (3) the extent of coordination between public organizations; and between public organizations and farmers. Data were collected by using household survey and semi-structured interview with key informants. Interviewed farmers implemented diverse measures aimed at increasing access to water, reducing their agricultural water needs and/or obtaining a non - agricultural income. Farmers often undertook a combination of adaptive actions. One third of interviewed farmers implemented first-best measures, i.e., measures that were not risky and enabled an income of the same range as the one they usually got before the drought. The other farmers could not implement first - best adaptive measures and chose second - best adaptive measures. Half of interviewed farmers chose at least one second-best measure (such as drilling a borehole) that involved high risks but could potentially lead to incomes of the same range as before the drought or even better. Other second-best measures implemented by farmers (such as initiating non- agricultural activities) were less risky but enabled limited income. The government provided material, technical, and financial supports, both to farmers individually and to some groups. Policies were designed and implemented based on coordination between public organizations, especially coordination between public organizations under the Ministry of Agriculture and Cooperatives, and the Ministry of Interior. Only one of the implemented policies (the support to collective income-generative projects) was designed using a participatory approach. In fact, few interviewed farmers benefitted from public support that had a sizable impact on their capacity to adapt to drought. Although the government supported many types of measures to help farmers during the drought in 2015 - 2016, there 'was a lack of linkage between these measures and the adaptation measures that farmers initiated to mitigate impacts of drought. In particular, most farmers lacked support to market other crops than rice, or to deal with the high uncertainty involved in most of the second-best measures they implemented. Based on the findings, capacity building of the sub - district administrative organizations to manage disasters is recommended, particularly focusing on the way to design community - based adaptations that will allow communities to cope with disaster prior to requesting external support. In addition, projects to support adaptation should be based on a bottom up approach of disaster management at a community level. This would lead to more efficient and inclusive disaster management.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Natural Resources Management, School of Environment, Resources and Development
Thesis (Ph.D.) - Asian Institute of Technology, 2019
Keywords: Droughts -- Thailand -- Suphanburi Province; Climatic changes -- Thailand -- Suphanburi Province; Hydrology -- Thailand -- Suphanburi Province